2012
DOI: 10.1111/j.1476-5381.2011.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescent histamine H1 receptor antagonist demonstrates the advantage of using fluorescence correlation spectroscopy to study the binding of lipophilic ligands

Abstract: BACKGROUND AND PURPOSEFluorescent ligands facilitate the study of ligand-receptor interactions at the level of single cells and individual receptors. Here, we describe a novel fluorescent histamine H1 receptor antagonist (mepyramine-BODIPY630-650) and use it to monitor the membrane diffusion of the histamine H1 receptor. EXPERIMENTAL APPROACHThe human histamine H1 receptor fused to yellow fluorescent protein (YFP) was transiently expressed in CHO-K1 cells. The time course of binding of mepyramine-BODIPY630-650… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…These profound differences in diffusion rates, allow the molecular composition of signalling complexes to be defined. To date, we have used fluorescent ligands in conjunction with FCS to characterize the adenosine A1 [12,44], adenosine A 3 [1,11] and histamine H 1 receptors [14], whereas other research groups have used the same approach to investigate β 2 -adrenoceptors [16], galanin [45] and somatostatin receptors [46]. In all FCS studies utilizing fluorescent ligands, ligand/receptor complexes have been found to exist as two distinct components within the autocorrelation trace (termed τ D2 and τ D3 ) with discrete rates of diffusion (typically 1–20 ms for τ D2 and 10–700 ms for τ D3 respectively) implying that multiple states or populations of receptors may exist at any one time.…”
Section: The Use Of Fluorescent Ligands In Fcsmentioning
confidence: 99%
See 1 more Smart Citation
“…These profound differences in diffusion rates, allow the molecular composition of signalling complexes to be defined. To date, we have used fluorescent ligands in conjunction with FCS to characterize the adenosine A1 [12,44], adenosine A 3 [1,11] and histamine H 1 receptors [14], whereas other research groups have used the same approach to investigate β 2 -adrenoceptors [16], galanin [45] and somatostatin receptors [46]. In all FCS studies utilizing fluorescent ligands, ligand/receptor complexes have been found to exist as two distinct components within the autocorrelation trace (termed τ D2 and τ D3 ) with discrete rates of diffusion (typically 1–20 ms for τ D2 and 10–700 ms for τ D3 respectively) implying that multiple states or populations of receptors may exist at any one time.…”
Section: The Use Of Fluorescent Ligands In Fcsmentioning
confidence: 99%
“…Typically within a trace, the faster component termed τ D1 (usually measured in microseconds), represents the photophysics of the fluorophore used or the free diffusion of a fluorescent ligand (if used), whereas more slowly diffusing species ( τ D2 , τ D3 ) represent molecular complexes (typically measured in milliseconds). FCS has been used by researchers in our laboratory to investigate the diffusion of a range of fluorescently tagged proteins including the Class A GPCRs adenosine A 1 [12,13], adenosine A 2A [13], adenosine A 3 [1,11], histamine H 1 [14] and neuropeptide (NPY) Y receptors [15]. FCS has also been used by other research groups to investigate β-adrenoceptors [16], somatostatin receptors [17], type 2 bradykinin [18] and the biogenic amine α 1b -adrenoceptors, β 2 -adrenoceptors, muscarinic M 1 and M 3 and dopamine D 1 receptors [19].…”
mentioning
confidence: 99%
“…However a significant limitation of the combined technique has been that FCS measurements are more problematic using YFP tagged proteins. Such measurements are limited by the more complex photophysics and increased photobleaching inherent to these GFP variants [28].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of FCS is that it can be used on a single cell level and actual amounts of ligand can be measured. This approach has been used for characterization of ligand binding to different GPCRs, including adenosine [20] and histamine [21] receptors, but the complexity of the equipment complicates its implementation in high throughput screening. FCS can also be used for assessment of the localization of receptors in different membrane domains within the cell, as well as the formation of complexes or aggregates of receptors [22].…”
Section: Fluorescence -Fcs and Famentioning
confidence: 99%